2013
DOI: 10.1016/j.molcel.2012.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Bacterial RNase YbeY Plays Key Roles in 70S Ribosome Quality Control and 16S rRNA Maturation

Abstract: Quality control of ribosomes is critical for cellular function since protein mistranslation leads to severe physiological consequences. We report the first evidence of a ribosome quality control system in bacteria that operates at the level of 70S to remove defective ribosomes. YbeY, a previously unidentified endoribonuclease, and the exonuclease RNase R act together by a process mediated specifically by the 30S ribosomal subunit, to degrade defective 70S ribosomes but not properly matured 70S ribosomes or ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
250
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(261 citation statements)
references
References 58 publications
9
250
2
Order By: Relevance
“…In trans complementation did not fully restore the growth rates at 4 and 42 u C. This could be due to inadequate expression of ybeY from the pMMB207 plasmid at these temperatures. Indeed, it was earlier found that the expression of ybeY is upregulated in E. coli at 45 u C (Jacob et al, 2013). Whether this could be valid for 4 u C is not known.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In trans complementation did not fully restore the growth rates at 4 and 42 u C. This could be due to inadequate expression of ybeY from the pMMB207 plasmid at these temperatures. Indeed, it was earlier found that the expression of ybeY is upregulated in E. coli at 45 u C (Jacob et al, 2013). Whether this could be valid for 4 u C is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to E. coli (Jacob et al, 2013), YbeY in Y. enterocolitica plays a role in rRNA maturation as a ybeY mutant causes misprocessing of 16S rRNA leading to its degradation, but does not have a visible effect on the 23S and 5S rRNA (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations